Ołeh Stecyszyn, Landsknechci Armii Halickiej, Lwów, Czasopys, 2012 (Олег Стецишин, Ландскнехти Галицької Армії, Львів, Часопис, 2012), 480 s. - Kozubel, Marek Bogdan (Pamięć i Sprawiedliwość, 2018)
recenzja